Ombudsman - Omoola, Sodiq (CLJ Publication, 2020)
The ombudsman concept has grown from being a medieval administrative mechanism into a modern tool for market regulation, dispute resolution, complaint handling, consumer protection and access to justice. This chapter examines the meaning and conceptual understanding of the ombudsman with emphasis on its origin and cultural underpinnings in selected legal traditions.